Characterization of tumor necrosis factor-a block haplotypes associated with susceptibility to chronic venous leg ulcers in Caucasian patients - Tan, J.; Price, Patricia; Gut, I.; Stacey, M.; Warrington, N.; Wallace, H. (Elsevier Inc., 2010)
Polymorphisms in the central major histocompatibility complex (MHC) are associated with several immunopathologic and inflammatory diseases, including chronic venous leg ulcers (CVLU). Because of strong linkage disequilibrium, identification of loci affecting disease susceptibility must be based on comparisons between haplotypes. Here we examine the association of conserved tumor necrosis factor (TNF) block haplotypes with CVLU susceptibility. A total of 171 Caucasian patients with CVLU were compared with 173 age-/gender-matched controls, excluding individuals with type 1 diabetes or rheumatoid arthritis. A total of 194 healthy subjects formed a separate population-based control group. Samples were typed for 38 tumor necrosis factor (TNF) block single nucleotide polymorphisms (SNP), human leukocyte antigen (HLA)-B and HLA-DRB1 alleles. TNF haplotypes were derived using the PHASE algorithm and assigned numbers (FVx) defined previously. The patients and matched controls shared 16 TNF block haplotypes. The patients had increased carriage of FV16 and alleles of the 8.1 and 60.3 MHC ancestral haplotypes (AH). CVLU risk is modulated by alleles within FV16 (e.g., TNF-308A and BAT1intron10 C insertion) or near FV16 in the 8.1AH. CVLU risk may also be mediated by unidentified alleles (not in FV22) marked by HLA-B40 and HLA-DR13. FV16 appears to be the best MHC and TNF block marker of susceptibility. After disease onset, an individual's TNF block haplotype does not modulate CVLU severity. © 2010 American Society for Histocompatibility and Immunogenetics.